Model Transportasi Terintegrasi Untuk Meningkatkan Efisiensi Tata Kelola Angkutan Umum Perkotaan (Studi Kasus: BRT Trans Jatim Porong–Sidoarjo–Surabaya) - Sri Wiwoho; Aristiono, Aristiono; Mayasari, Sri (Universitas Veteran Bangun Nusantara, 2025)
This study aims to design an integrated transportation model to improve the efficiency of urban public transportation governance, with a case study on the Bus Rapid Transit (BRT) Trans Jatim corridor Porong–Sidoarjo–Surabaya. The study uses a quantitative approach with a simple linear regression method. Data were collected through questionnaires distributed to BRT users and analyzed using SPSS software. The analysis showed that mode integration has a significant influence on the efficiency of public transportation governance, with a correlation coefficient (R) of 0.800 and a determination coefficient (R²) of 0.640. The significance test showed a Sig. value of 0.009. The resulting regression equation is Y = 0.694 + 0.834X. This model indicates that increased integration in transportation can significantly enhance the efficiency of public transportation system management.